ESTIMATING EARTHQUAKE MAGNITUDE USING SPATIAL INTERPOLATION WITH THE INVERSE DISTANCE WEIGHTING AND ORDINARY KRIGING APPROACH - Amalia, Fitri; Fauzan, Achmad (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
The West Java region is known for its high disaster vulnerability, particularly to earthquakes, due to the presence of many active faults. Based on this, information is needed as an initial step for disaster mitigation to reduce disaster risk and guarantee community safety in the West Java region, one of which is by carrying out spatial interpolation. In this study, the Inverse Distance Weighted (IDW) and Ordinary Kriging (OK) methods were used. The research sample included data on earthquake magnitude in West Java within the same coordinate range, from 01 January 2022 to 31 December 2022. This research was conducted to find out a more precise spatial interpolation method in estimating the strength of the earthquake in West Java in 2022. From the OK analysis results, the best theoretical semivariogram model was obtained, namely the Exponential model with nugget, sill and range values ​​of 0.07, 0.12 and 11451 meters. From the results of the IDW analysis, the best power value parameter was obtained, namely 2. This research was conducted to develop a more precise spatial interpolation method for estimating earthquake strength in West Java in 2022. The OK method results indicated that most of the West Java region has the potential for earthquakes with a magnitude of around 1.5 to 4.0, while the IDW method suggested a potential magnitude of around 2.0 to 4.0. The potential for a high-magnitude earthquake is in Kp. Cileuley, Garumukti, Pamulihan District, Garut Regency, West Java. Based on the results of Holdout Cross Validation, the IDW method is the best for estimating earthquake magnitude in West Java, with a MAPE value of 17.8%. The IDW method's estimation of earthquake magnitude is superior to OK, with smaller MAPE and MAE values.